Adsorption behavior of methylene blue on graphene and hexagonal boron nitride monolayers in aqueous solution: A first-principles treatment. (March 2023) - Liu, Huazhong; An, Qing; Deng, Qian; Ming, Jiexiu; Xu, Han
Abstract: Understanding the adsorption of dye molecules on nanostructured materials is important in regard to innovative potential applications, especially when the corresponding entities are combined. Here, we explore the interaction of methylene blue (MB) with graphene and hexagonal boron-nitride (h-BN) as two-dimensional nanosheets with unique electronic properties and high potential in technological applications. We study these interactions using quantum-based molecular simulations and probe these through the interaction properties and electronic structure of the adsorbed MB on the considered monolayers and especially the specific role of the surrounding environment. We discuss the importance of the findings in view of contaminant removal from wastewater and specifically sensing applications of considered monolayers. Our dispersion-corrected density functional theory (DFT) results show that MB adsorbs strongly on both the graphene and h-BN with interaction energies of −47.454 and −45.072 kcal/mol, respectively, with equilibrium distances of about 3.2 Å between the aromatic rings of adsorbate and substrates. The accuracy of the DFT calculations is validated by the coupled-cluster with single, double (triple) excitations level of theory. The charge density and atom-in-molecule theory analyses reveal the existence of non-covalent and electrostatic interactions between MB and graphene/h-BN surface. The electronic structure analysis shows that the semiconducting graphene becomes metallic after MB adsorption while the h- BN monolayer retains its semiconducting characteristic upon the adsorption. Complementary assays using DFT-based molecular dynamic simulations demonstrate the strong binding of MB to both the graphene and h-BN surfaces in the presence of water molecules as competitive entities. These findings demonstrate the potential applications of graphene and h-BN for the efficient adsorption of dye molecules and for developing promising adsorbents for wastewater treatment and functionalized sensors. Graphical abstract: Image 1 Highlights: DFT simulations were used for interaction of methylene blue (MB) with graphene and h-BN monolayers. MB adsorbs strongly on both the substrates with interaction energies of about −50 kcal/mol. Interaction natures are typical for the physisorption according to the AIM theory. The band gap was vanished in the graphene after MB adsorption in contrast to the h-BN system. Behavior of adsorbed MB on graphene/h-BN at aqueous solution is evaluated by DFT‒MD simulation.